Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Topic : Linear equations in two variables.
Given :
- 2x - y = 3 ––– (i)
- - x - y = 3 ––– (ii)
Solution :
Now,
(i) – (ii)
[tex]\qquad \sf \: { \dashrightarrow 2x - y - ( - x - y) = 3 - 3}
[/tex]
[tex]\qquad \sf \: { \dashrightarrow 2x - y + x + y) = 3 - 3}
[/tex]
[tex]\qquad \sf \: { \dashrightarrow 3x = 0}
[/tex]
[tex]\qquad \bf \: { \dashrightarrow x = 0}
[/tex]
Now, substituting the value of x in Eq (i) :
[tex]\qquad \sf \: { \dashrightarrow 2x - y = 3 }[/tex]
[tex]\qquad \sf \: { \dashrightarrow 2(0)- y = 3 }[/tex]
[tex]\qquad \sf \: { \dashrightarrow 0- y = 3 }[/tex]
[tex]\qquad \bf \: { \dashrightarrow y = - 3 }[/tex]
Therefore,
- The value of x = 0 and y = -3
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.